Penguatan Kapasitas Panitia Pengawas Pemilu Kecamatan pada Pemilihan Umum Tahun 2024 di Kabupaten Nagan Raya - Fadhil Ilhamsyah; Faez Syahroni; Fadhly, Zuhrizal; Husna , Cut Asmaul; Sudarman; Najamudin (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The Sub-district Election Supervisory Committee (Panwascam) is one of the important instruments that will determine the quality of the election process at the sub-district level. This service was carried out because, based on experience from the implementation of previous elections, there are still Panwascam members who do not carry out their duties, authorities, and obligations as stipulated in the laws and regulations. Therefore, it is important to do community service in the form of Technical Guidance (Bimtek) with the implementer of Panwaslih Nagan Raya and present the author as a resource person. The lecture method, the use of laptops and LCD media to display power point material regarding the duties, powers, and obligations of Panwascam based on Law Number 7 of 2017 concerning General elections, and tips for becoming a successful Panwascam. The results achieved through this community service activity are: First, Panwascam in Nagan Raya Regency as election supervisors in the sub-district area have an understanding of their duties, authorities, and obligations and are successful in carrying out supervision in the 2024 Simultaneous Elections. Second, to motivate Panwascam in Nagan Raya Regency to be able to carry out election supervision in the sub-district area in a direct, general, free, confidential, honest, and fair manner. Third, in the future, it is necessary to hold regular technical guidance for Panwascam with the theme of general supervision and supervision of each stage of the Election, so that the task of supervising the Simultaneous Election in 2024 will be better, stronger, and more effective.